Self-presentation of non-philological students: Speech genre and linguistic aspects - Veselkova , Tatyana Vyacheslavovna (Жанры речи, 2021)
The analysis of the speech genre of self-presentation is performed within the anthropocentric approach to the language and speech. The study focuses on the self-presentation of non-philological students. The research is based on the comparative analysis of the papers of first year students and graduate students of the faculties of geography and of computer science and information technology, as well as of the Institute of physical education and sports of Saratov National Research State University. A multi-aspect analysis of student self-presentations revealed the main features of the speech genre of self-presentation. Among them are the most typical cognitive models (scenarios) of self-presentation which form the basis of the corresponding speech genre. In student papers, the speech genre of self-presentation often interacts with other speech genres: appeals, messages, and gratitude. First year students demonstrate a strategy that suggests an effort to please, to appear attractive to others. Graduate students present a strategy of self-promotion, trying to prove their professional competence. The analyzed papers show that the students demonstrate the awareness that effective self-presentation is based on verbal-logical and emotional-expressive elements of speech which act as the means of linguistic persuasion. The papers abound in clichés and set expressions containing elements of formal academic style.